Complicaciones del recién nacido asociados al uso de ventilación mecánica. - Guevara Quevedo, César Enrique (2016)
An observational, retrospective, transversal study was conducted in patients admitted to the intensive care unit of Isidro Ayora Loja requiring mechanical ventilation for more than 24 hours for the years 2013-2014 Hospital. The objectives were to determine what are the complications newly born associated with the use of mechanical ventilation in the neonatal intensive care Isidro Ayora Hospital of Loja, set the type of used mechanical ventilation, determine what were the complications in the newborn according to gender, weight, gestational age and relate time ventilation complications.The results are the complications that occurred most frequently was the retinopathy of prematurity (41.24%) and bronchopulmonary dysplasia (37.11%). The type of mechanical ventilation was used invasive mechanical ventilation (67%).Complications occurred more in the masculine gender, gestational age was 35-36 and 32-34 predominance weeks, 43.29% of newborns had weight between 1500 to 2500 grams, time 6-10 days of mechanical ventilation was the day of onset of complications with the highest percentage with 29.90%. Keywords: complications, mechanical ventilation, neonates